Variations in the Structure and Evolution of Rice WRKY Genes in Indica and Japonica Genotypes and their Co-expression Network in Mediating Disease Resistance. (June 2019) - Jimmy, John Lilly; Babu, Subramanian
WRKY transcription factor (TF) family regulates many functions in plant growth and development and also during biotic and abiotic stress. In this study, 101 WRKY TF gene models in indica and japonica rice were used to conduct evolutionary analysis, gene structure analysis, and motif composition. Co-expression analysis was carried out first by selecting the differentially expressing genes that showed a significant change in response to the pathogens from Rice Oligonucleotide Array Database (ROAD). About 82 genes showed responses to infection by Magnaporthe oryzae or Xanthomonas oryzae pv. oryzae . Co-expression gene network was constructed using direct neighborhood and context associated inbuilt mode in RiceNetv2 tool. Only 41 genes showed interaction with 2299 non- WRKY genes. Variations exist in the structure and evolution of WRKY genes among indica and japonica genotypes which have important implications in their differential roles including disease resistance. WRKY genes mediate a complex networking and co-express along with other WRKY and non- WRKY genes to mediate resistance against fungal and bacterial pathogens in rice.